2021
DOI: 10.1002/oby.23170
|View full text |Cite
|
Sign up to set email alerts
|

Increased Brain Reward Responsivity to Food‐Related Odors in Obesity

Abstract: Objective Food odors serve as powerful stimuli signaling the food quality and energy density and direct food‐specific appetite and consumption. This study explored obesity‐related brain activation in response to odors related to high‐ or low‐energy‐dense foods. Methods Seventeen participants with obesity (BMI > 30 kg/m2; 4 males and 13 females) and twenty‐one with normal weight (BMI < 25 kg/m2; 9 males and 12 females) underwent a functional magnetic resonance imaging scan in which they received chocolate (high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Furthermore, we found that the number of OC patients classified as hyposmic is significantly higher than the number of HC hyposmic subjects, suggesting that both the general and specific olfactory performance for odor discrimination and identification skills are more impaired in patients than in controls. Likewise, it was previously found that participants with obesity, compared to normal weight controls, have a reduced ability to discriminate odors [ 61 ], that a lower BMI is associated with a better ability to identify odors [ 51 ], and that people with obesity achieve lower TDI olfactory scores [ 52 ]. Instead, we did not find a significantly reduced ability in the olfactory threshold, although we did observe a decline in olfactory sensitivity in patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the number of OC patients classified as hyposmic is significantly higher than the number of HC hyposmic subjects, suggesting that both the general and specific olfactory performance for odor discrimination and identification skills are more impaired in patients than in controls. Likewise, it was previously found that participants with obesity, compared to normal weight controls, have a reduced ability to discriminate odors [ 61 ], that a lower BMI is associated with a better ability to identify odors [ 51 ], and that people with obesity achieve lower TDI olfactory scores [ 52 ]. Instead, we did not find a significantly reduced ability in the olfactory threshold, although we did observe a decline in olfactory sensitivity in patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed research on ASR-related behaviors, characteristics, traits and processes has expanded considerably in recent years and there is now a growing set of possibilities for inclusion in research about ASR phenotypes in childhood including: temperament (such as impulsivity and effortful control) ( 90 ), Executive function (such as inhibitory control), genetic susceptibility, reward sensitivity, hedonic responses to food, cognitive function ( 91 ), cognitive control and negative affect ( 92 ), state and/or trait food cue reactivity ( 93 ), brain reward sensitivity to food cues ( 94 ), dietary measures, such as dietary fat or carbohydrates ( 95 , 96 ), fructose consumption ( 97 ), intake of processed food ( 98 ), sensory sensitivity ( 99 ), neuroimaging functional connectivity ( 100 ), metabolomics and analysis of the gut microbiome ( 101 , 102 ), measures of the social facilitation of eating ( 103 ), susceptibility to modeling ( 104 ), effects of portion size cues ( 105 ) and attachment security ( 106 ), behavioral and neural measures of appetitive traits such as through neuroimaging measures ( 107 , 108 ). A helpful broadening of work on ASR phenotypes is also suggested by attention to endophenotypes where genetic predisposition and neural substrates as well as behavioral measures are included ( 107 , 109 112 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although incentive salience is primarily a motivational phenomenon, it also comprises attentional, affective, learning-related, and behavioral facets. Consistently, functional magnetic resonance imaging (fMRI) studies using cue reactivity (CR) tasks did not only find striatal hyperresponsivity to high-calorie food cues but also a hyperresponsivity in anterior cingulate cortex and visual areas, amygdala, orbitofrontal cortex, and hippocampus [ 77 80 ]. CR tasks represent the key functional paradigms for studying incentive salience which contrast neural signals emerging during perception of food cues to those during control conditions (see 3.1.1).…”
Section: Central Nervous Mechanisms Affecting Body Weightmentioning
confidence: 95%